Reducing the vulnerability of Pacific ACP states - Martin, Franck (Technical Centre for Agricultural and Rural Cooperation, 2003)
The South Pacific Applied Geoscience Commission (SOPAC) successfully uses Geographical Information Systems (GIS) technology for water risk management purposes.